Families created through transracial adoption: parents' and teachers' discourses at selected Gauteng schools - Robinson, Kelly J (My University, 2018)
Family is just family? This research sought to establish how the language which is used by parents of transracially adopted children, as well as the teachers who teach them, constructs the idea of family, through the language which is used within the conversations of these respective parties. The research was conducted through semi-structured interviews with parents of transracially adopted children who had responded to a Facebook request for research participants. Teachers from four private, primary schools in Johannesburg formed the second set of interview participants. Applied Thematic Analysis was used to analyse the interviews, taking a narrative approach to interpret the stories that emerged. It was within the gaps and overlaps in conversations with parents and teachers that the revealing content emerged. Two of the most telling aspects which arose in this research were the extent to which heteronormative privilege reaches within family units and extends into the school environment and school application process. The other aspect which arose and which was explored in various sections of the research was in fact race. Did parents consider this when they adopted transracially and how do they speak about race in conversations with their transracially adopted children? For teachers the question was how they engage in conversations about race in the classroom, taking into account all the possible dynamics at play, as well as considering the position of the transracially adopted child. Different stances and manners of interacting or retreating from the topic are elucidated. This research found that there needs to be an ongoing conversation with all key role players involved in the process of adoption and specifically those involved in transracial adoption. The chasm between the theoretical ideas of what constitutes a family and the reality of what is expressed in relation to this dynamic needs to be bridged through the advancement and development of a sophisticated vocabulary which can be employed in future conversations.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy (Critical Diversity Studies) October 2018
Keywords: Interracial adoption--South Africa; Adopted children--South Africa